Royal murder : the deadly intrigue of ten sovereigns - MacLeod, Elizabeth (New York : Annick Press, 2008)
Profiles ten sovereigns, some who avoided death and others who caused it, who became some of the most notorious rulers of history, including Cleopatra, Vlad the Impaler, and Marie Antoinette.
Includes bibliographical references (p. 122-123) and index.
7.5
5-8
Keywords: Assassination -- Juvenile literature; Kings and rulers -- Juvenile literature; Murder -- Juvenile literature; Assassination; Kings, queens, rulers, etc; Murder; Assassination; Homicide; Kings and rulers